Taspoglutide, a once‐weekly glucagon‐like peptide 1 analogue, vs. insulin glargine titrated to target in patients with Type 2 diabetes: an open‐label randomized trial. Issue 1 (13th December 2012) - Nauck, M.; Horton, E.; Andjelkovic, M.; Ampudia‐Blasco, F. J.; Parusel, C. T.; Boldrin, M.; Balena, R.; ,
Abstract Aims To compare the efficacy and safety of once‐weekly taspoglutide with insulin glargine in patients with advanced Type 2 diabetes failing metformin and sulphonylurea combination therapy. Methods This open‐label, parallel‐group, multi‐centre trial randomized 1049 patients continuing metformin 1:1:1 to taspoglutide 10 mg once weekly, taspoglutide 20 mg once weekly or insulin glargine once daily with forced titration to fasting plasma glucose ≤ 6.1 mmol/l. Sulphonylureas were discontinued before randomization. The primary endpoint was change in HbA1c after 24 weeks. Results After 24 weeks, least‐square mean changes from baseline in HbA1c in patients receiving taspoglutide 10 mg [−8 mmol/mol (se 1)] [−0.77% (se 0.05)] or taspoglutide 20 mg [−11 mmol/mol (se 1)] [−0.98% (se 0.05)] were non‐inferior to insulin glargine [−9 mmol/mol (se 1)] [−0.84% (se 0.05)]; treatment difference of 0.07% (95% CI −0.06 to 0.21) and −0.14% (95% CI −0.28 to −0.01), for taspoglutide 10 and 20 mg, respectively, vs. insulin glargine. Taspoglutide was associated with more adverse events (mainly gastrointestinal) and significantly less hypoglycaemia than insulin glargine. Conclusions Compared with insulin glargine, taspoglutide provided non‐inferior HbA1c reductions associated with less hypoglycaemia, but more gastrointestinal adverse events.